2016
DOI: 10.1016/j.csbj.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Translation in Mammalian Cell Factories to Increase Protein Yield: The Unexpected Use of Long Non-Coding SINEUP RNAs

Abstract: Mammalian cells are an indispensable tool for the production of recombinant proteins in contexts where function depends on post-translational modifications. Among them, Chinese Hamster Ovary (CHO) cells are the primary factories for the production of therapeutic proteins, including monoclonal antibodies (MAbs). To improve expression and stability, several methodologies have been adopted, including methods based on media formulation, selective pressure and cell- or vector engineering. This review presents curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 114 publications
(127 reference statements)
0
24
0
1
Order By: Relevance
“…As shown earlier, lncRNAs are deemed to be an essential regulator in almost all biological processes. Moreover, a recent study reported that a family of antisense lncRNAs (SINEUPs) are able to increase translation of partially overlapping protein‐coding messenger RNAs (mRNAs) (Zucchelli et al ., ). Therefore, it is valuable to know whether lncRNAs relate to silk yield variation between domestic and wild silkworms.…”
Section: Introductionmentioning
confidence: 97%
“…As shown earlier, lncRNAs are deemed to be an essential regulator in almost all biological processes. Moreover, a recent study reported that a family of antisense lncRNAs (SINEUPs) are able to increase translation of partially overlapping protein‐coding messenger RNAs (mRNAs) (Zucchelli et al ., ). Therefore, it is valuable to know whether lncRNAs relate to silk yield variation between domestic and wild silkworms.…”
Section: Introductionmentioning
confidence: 97%
“…As the majority of the lncRNAs reported in the literature are discussed and related to human or model organism systems, our work aimed at unveiling the role of lncRNAs in CHO under industrially relevant conditions to identify new targets for manipulation to sustain proliferation. Examples of successful cell engineering of lncRNAs to selectively enhance translation and product yield have already been reported in CHO, demonstrating the potential of manipulation of lncRNAs for enhancing industrial processes. Moreover, since it was reported up to 15% of the total ribosome occupancy can be occupied by a single recombinant mRNA, the intrinsic characteristics of lncRNAs place them as ideal candidates for cell line engineering of protein production cell factories, as they do not add any translational burden on top of the coding gene of interest…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of lncRNAs in controlling cellular processes, and unlike small non‐coding RNAs (e.g., siRNAs, microRNAs), the impact(s) of lncRNA expression on CHO cell bioprocessing with regard to growth/proliferation and recombinant protein yields and quality has barely been explored, with only a small number of studies reported . However, these two studies show that manipulation of lncRNAs can impact upon recombinant protein production from CHO cells.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are able to regulate manyfold cellular processes (Geisler & Coller, ; Wang & Chang, ) and became as well of interest for cell line engineering as a lncRNA with a complementary sequence to the NF‐kappa‐B inhibitor alpha (NFKBIA) was identified to enhance culture longevity and productivity when stably overexpressed (Tabuchi, ). Moreover, so called SINEUP lncRNAs are of great potential for cell line engineering as they can be designed to target a specific mRNA to increase translation (Zucchelli, Patrucco, Persichetti, Gustincich, & Cotella, ). However, the function of the vast majority of lncRNAs is still unknown complicating the analysis of potential pathways induced by these RNA molecules.…”
Section: Discussionmentioning
confidence: 99%